2013
DOI: 10.1103/physreve.87.033013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shear on Rayleigh-Taylor mixing at small Atwood number

Abstract: The effect of shear on the development of Rayleigh-Taylor instability is studied at an Atwood number of 0.035 using the gas tunnel at Texas A&M University. Two types of diagnostics, imaging and simultaneous hot wire and cold wire anemometry are used to measure mix widths, point wise instantaneous velocities, and density. Image analysis has shown that the superposition of shear on Rayleigh-Taylor instability development increases the mixing width and growth rate at early times

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…A possible explanation could be that, at low Atwood numbers, the effect of shear velocities and secondary instabilities is more representative and could change the rate of evolution of the Rayleigh-Taylor instability. Actually, this has been experimentally studied only in 2013 by Akula, Andrews and Ranjan [15], who found that shear effects in Rayleigh-Taylor instability increase the evolution rate for low Atwood Numbers, in agreement with Fig. 5.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…A possible explanation could be that, at low Atwood numbers, the effect of shear velocities and secondary instabilities is more representative and could change the rate of evolution of the Rayleigh-Taylor instability. Actually, this has been experimentally studied only in 2013 by Akula, Andrews and Ranjan [15], who found that shear effects in Rayleigh-Taylor instability increase the evolution rate for low Atwood Numbers, in agreement with Fig. 5.…”
Section: Resultssupporting
confidence: 63%
“…The effect of the Atwood number on the rate of evolution of the instability follows the theoretical expression only for high Atwood numbers; deviations at low numbers have been recently found by experimentalists [15]. One possible explanation is the onset of secondary Kelvin-Helmoltz instabilities, which are more representative at low Atwood numbers and could increase the rate of evolution of the Rayleigh-Taylor instability.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The injected fog is used as a light extinction medium for the light coming from the LED panels. Before the experiment, it is ensured that the absorption due to fog is linearly proportional (thin-medium approximation of the Beer-Lambert law (Akula, Andrews & Ranjan 2013)) to the volume fraction of the fog for the camera settings and the fog flow rate using the wedge calibration technique of Banerjee & Andrews (2006). This calibration is necessary for obtaining the volume fraction contours from the visualization.…”
Section: Visualizationmentioning
confidence: 99%
“…In particular, they showed that turbulent mixing increases significantly either at large scale, by shear, in case of sheared and neutrally stratified flow or at both large and small scales, by buoyancy, in case of unsheared and unstably stratified flow. Akula et al (2013) reported that the mixing layer is initially dominated by shear associated with roller vortices originating from Kelvin-Helmholtz instability and further downstream the mixing layer is governed by buoyancy with vertical plume structures originating from Rayleigh-Taylor instability. Transition occurs within a wide critical bulk Richardson number range (Ri b from −1.5 to −2.5) for an Atwood number A = 0.035 (A = ρ1−ρ2 ρ1+ρ2 where ρ 1 is the density of the heavier fluid and ρ 2 the density of the lighter fluid).…”
Section: Effects Of Stratificationmentioning
confidence: 99%